1,4-Anhydro-2-C-benzyloxymethyl-2,3 : 5,6-di-O-isopropylidene-D-tallitol - Watkin, D; Parry, L; Soengas, R; Fleet, G (2005)
The crystal structure of the title compound, C20H 28O6, allows a firm assignment of the stereochemistry at C-4 of formation of the tetrahydrofuran (THF) ring. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.